Impacto económico y el comercio informal en comerciantes del Mercado Modelo 3 de Octubre Iquitos año 2024 - Grandez Tello, Gabriela Celeste (2025)
The present research work entitled "Economic impact and informal trade on merchants of the Mercado Modelo 3 de Octubre Iquitos year 2024", was developed with the objective of determining the level of economic impact of informal trade on merchants of the Mercado Modelo 3 de Octubre Iquitos year 2024, the research was descriptive, with a non-experimental design, and the study population was considered to be 61 merchants who voluntarily decided to participate in this research work, to whom the survey technique was assigned and the questionnaire as an instrument; After analyzing the results, it was determined that 47.9% belong to informal trade and 52.1% are formalized merchants. Regarding economic impact, 44.8% have a direct impact on medium-level formal merchants, and 55.2% have a medium level that does not impact formal trade. It was concluded that informal merchants in the 3 de Octubre Iquitos market in 2023 have a direct impact on medium-level formal merchants.